Post-War Armenia: Crisis of Confidence and Role of Social Capital in this Context - Saribekyan, Amalya (Bulletin of Yerevan University G: Economics, 2022)
New approaches and non-standard solutions have become a necessity in this rather complicated modern post-war period of the country. The article points out how to overcome the problems that have arisen in the country and achieve a new qualitative level of the development. This study is noteworthy for its interconnected observation and systematic approach to existing problems and their solutions in the social-economic and moral-psychological spheres. The article focuses on the cause-and-effect manifestations of the crisis of confidence created in post-war Armenia and the issues to overcome it. In this context social capital is viewed as a starting point for overcoming the post-war situation in Armenia.Admitting that it is not easy to create such conditions to achieve consolidation and harmonious cooperation, so that the synergistic effect of social capital is fully manifested and provides a breakthrough in the political, moral-psychological, socio-economic crisis situation, however, as evidenced by the experience of many succeeded countries, this is possible.Here, both the role of the society as a guarantee of overcoming the atmosphere of mistrust and polarization in the country, and the role of the state as a guarantor of overcoming the crisis of trust and the country's withdrawal from the current situation are very important.This approach, via mutual trust and consolidation, will provide us with the opportunity to achieve the mobilization and effective implementation of our national potential, as well as to increase the country's viability as quickly as it is possible.
Keywords: post-war Armenia; social-economic situation; moral-psychological situation; crisis of confidence; social capital; mutual trust; public consolidation; social- economic development